2022
DOI: 10.1007/s11665-021-06547-w
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Retained Austenite on the Mechanical Properties of Bainitic and Dual Phase Steels

Abstract: This paper presents the microstructural changes and mechanical properties of carbide-free bainitic steel subjected to various heat treatment processes and compares these results with similarly treated ferritic–pearlitic steel. A key feature of the investigated steel, which is common among others described in the literature, is that the Si content in the developed steel was >1 wt.% to avoid carbide precipitation in the retained austenite during the bainitic transformation. The phase identification before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
3
0
1
Order By: Relevance
“…Porosity analysis by less steel demonstrated a predominately martensitic microstructure, with some reverted inter-lath austenite formed in the heat-affected areas throughout printing [23,36]. The reverted austenite induces the transformation-induced-plasticity (TRIP) effect, where austenite transforms to martensite throughout plastic deformation, resulting in reduced yield strength and increased ductility commonly among steels [42]. The non-lath austenitic regions are most evident in Scanning Electron Microscopy (SEM) imaging as displayed in Figure 3, contrasting the cast martensite microstructure in Figure 2 Energy Dispersive Spectroscopy (EDS) analysis identifies the formation of Niobium Carbide (NbC) precipitates up to 10 μm in size, responsible for high-stress sites and subsequent cracks.…”
Section: As-fabricated Microstructure and Porosity Of 17-4ph Stainles...mentioning
confidence: 99%
“…Porosity analysis by less steel demonstrated a predominately martensitic microstructure, with some reverted inter-lath austenite formed in the heat-affected areas throughout printing [23,36]. The reverted austenite induces the transformation-induced-plasticity (TRIP) effect, where austenite transforms to martensite throughout plastic deformation, resulting in reduced yield strength and increased ductility commonly among steels [42]. The non-lath austenitic regions are most evident in Scanning Electron Microscopy (SEM) imaging as displayed in Figure 3, contrasting the cast martensite microstructure in Figure 2 Energy Dispersive Spectroscopy (EDS) analysis identifies the formation of Niobium Carbide (NbC) precipitates up to 10 μm in size, responsible for high-stress sites and subsequent cracks.…”
Section: As-fabricated Microstructure and Porosity Of 17-4ph Stainles...mentioning
confidence: 99%
“…[10,16] These also contain the so-called blocky retained austenite, and due to its low thermal stability, it may be fully or partially transformed into martensite during continuous cooling, forming M/A islands. [10] Also, Adamczyk-Cies´lak et al [17] compared the mechanical properties of bainitic steel rails after isothermal heat treatment and continuous cooling processes. It was found that low-carbon steel after a continuous cooling process is characterized by a more favorable combination of strength and elongation compared to the isothermally heat treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…In just 2 years, significant research reports have been published in terms of low-carbon bainitic steels intended for applications in railway infrastructure. The latest investigations cover a wide range of issues including microstructure optimization considering alloying additives [1] and processing techniques [2]; manufacturing process [3]; heat treatments methods [4]; wear resistance [5]; rolling contact fatigue [6]; lowcycle fatigue performance [7]; fatigue crack growth rate [8]; and analysis of welding processes [9]. The mechanical properties of bainitic steels, compared with those of conventional ones, are promising and * E-mail: aleksandra.krolicka@pwr.edu.pl indicate the possibility of enhancing the durability of railway tracks, especially under heavy loads.…”
Section: Introductionmentioning
confidence: 99%